Implementasi IT dalam Pembelajaran Siswa Kelas VII SMP Katolik St. Aloysius - Mersiana Delu Ngara; Vinsensius Aprila Kore Dima; Sihang Gregorius Balimema (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information technology (IT) has made a significant contribution to the field of education, including at the junior high school level. This study aims to examine the implementation of information technology in the learning process of seventh-grade students at SMP Katolik St. Aloysius. The research method applied was descriptive qualitative, employing observation, teacher interviews, and student questionnaires. The findings indicate that the use of IT tools such as computers, LCD projectors, and online learning applications, particularly Google Classroom and WhatsApp Groups, has enhanced student learning motivation, facilitated easier access to learning materials, and strengthened interaction between teachers and students. Moreover, technology integration enables teachers to deliver more engaging and varied learning experiences, encouraging students to participate more actively in the classroom. Nevertheless, several challenges were identified, including limited school infrastructure, varying levels of digital literacy among students, and unequal internet access. These obstacles may hinder the effectiveness of IT implementation in the learning process. Therefore, continuous mentoring strategies, infrastructure improvement, and digital literacy training for both students and teachers are necessary. In conclusion, the implementation of information technology at SMP Katolik St. Aloysius has had a significant positive impact on the learning process but requires sustainable support and improvements to achieve optimal outcomes